A sodium ion negative electrode material MoP@TiO 2 Preparation method
By using MoP and TiO2 in sodium ion batteries, the structural crushing problem caused by volume changes in the negative electrode material during the reaction process is solved, and high electrochemical capacity and excellent cycling and rate performance are achieved.
Patent Information
- Application Number
- CN202211023982.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-08-24
AI Technical Summary
The negative electrode materials of existing sodium ion batteries are prone to irreversible volume changes during the reaction process, resulting in the pulverization of the electrode structure and poor cycle stability and rate performance.
Through a simple ion coordination method, the coated MoP and TiO2 are grown in situ to achieve their close bond. TiO2 improves conductivity and buffers volume expansion, and regulates the titanium source to obtain MoP@TiO2 composite material with excellent electrochemical properties.
The high electrochemical capacity and excellent cycle performance and rate performance of MoP@TiO2 composite materials are achieved, which avoids the complexity and toxicity of traditional methods, and greatly shortens the preparation cycle.
Smart Images

Figure CN115275158B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery electrode materials, and specifically relates to a method for preparing a sodium ion negative electrode material MoP@TiO2. Background Art
[0002] With the growth of energy demand, electrochemical energy conversion and storage technology (EECS) has received extensive attention. Secondary battery systems represented by lithium-ion batteries and sodium-ion batteries have the advantages of high energy density, high operating voltage, and stable charge and discharge, and are new energy systems with great potential. Sodium-ion batteries (SIBs) are expected to become an alternative to lithium-ion batteries (LIBs) due to their similar electrochemical principles and wider sodium reserves. At present, many transition metal oxides and hard carbon materials have been used as anode materials for SIBs, but their specific capacity and cycle life cannot meet the stringent requirements of electronic devices and large-scale energy storage. Therefore, it is necessary to explore more suitable anode materials with excellent electrochemical properties to further optimize SIBs technology.
[0003] Molybdenum phosphide (MoP) has been studied quite extensively in hydrogen evolution reaction due to its high catalytic activity and excellent electrochemical performance. Nevertheless, due to its relatively complex synthesis process, few studies have focused on it as anode material for sodium-ion batteries. In fact, MoP can also be used as anode material with a high theoretical specific capacity of 632 mAhg -1 However, MoP also suffers from severe irreversible volume changes during a wide range of reactions. This inevitable obstacle leads to structural pulverization of the electrode, resulting in poor cycle stability and rate performance. The most effective solution is to construct a highly conductive composite material by combining it, so the further introduction of titanium dioxide enhances the interfacial reaction and structural stability. Titanium dioxide not only increases the speed of electron movement around the active material, but also acts as a volume buffer to relieve structural strain, which is beneficial to battery performance. Some studies have shown that constructing composite materials can expand the lattice space, which is beneficial to Na + The insertion / extraction of the electrode can resist volume expansion / contraction, thus achieving better electrochemical performance.
[0004] The conventional preparation method of MoP@TiO2 material is to first prepare Mo-based compounds, then produce PH3 phosphating through thermal decomposition of NaH2PO2 to obtain pure phase MoP material, and then introduce titanium dioxide using electrospinning. This preparation method is relatively complicated and highly toxic, requiring strict control of the sealing of the reaction device and the subsequent product separation, and the preparation cycle is relatively long. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a sodium ion negative electrode material MoP@TiO2, which is simple and environmentally friendly, has mild and easy-to-control synthesis conditions, a short preparation cycle, and a high electrochemical capacity of the prepared product. When it is used as a sodium ion negative electrode material, it can exhibit excellent electrochemical performance.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a sodium ion negative electrode material MoP@TiO2, comprising the following steps:
[0007] (1) dispersing a molybdenum source and a phosphorus source into deionized water and stirring at room temperature to form a uniform mixed solution;
[0008] (2) adjusting the pH of the mixed solution to 1-3 and then loading it into a pressure tube, setting the reaction temperature and reaction time to carry out the coordination reaction;
[0009] (3) washing and drying the mixed solution after the reaction in step (2) to obtain a Mo-based MOF compound;
[0010] (4) adding a titanium source to the Mo-based MOF compound to obtain a titanium source-coated Mo-based MOF compound composite material precursor;
[0011] (5) The precursor prepared in step (4) is subjected to high-temperature sintering heat treatment in a sintering atmosphere to obtain a MoP@TiO2 composite material.
[0012] Preferably, in step (1), the concentrations of the molybdenum source and the phosphorus source in the mixed solution are 0.05-0.3 mol / L respectively.
[0013] Preferably, in step (1), the molybdenum source is one of sodium molybdate, ammonium molybdate, and molybdenum chloride; and the phosphorus source is one of p-phenylene diphosphonic acid, phytic acid, and phenylphosphonic acid.
[0014] Preferably, in step (2), the reaction temperature is 100-200° C. and the reaction time is 10-20 h.
[0015] Preferably, in step (2), the pH value of the mixed solution is adjusted by concentrated hydrochloric acid.
[0016] Furthermore, in step (3), the mixed solution after the reaction in step (2) is washed with deionized water for 2-5 times and with anhydrous ethanol for 1-3 times, and then dried in a vacuum atmosphere at 60-100° C. for 6-8 hours.
[0017] Preferably, in step (4), the titanium source is 20-60% by mass of the Mo-based MOF compound.
[0018] Preferably, in step (4), the titanium source is one of tetraisopropyl titanate, tetrabutyl titanate and titanium tetrachloride.
[0019] Furthermore, in step (4), the Mo-based MOF compound is dispersed in anhydrous ethanol with stirring, and concentrated ammonia water is added to obtain solution I; the titanium source is dispersed in anhydrous ethanol to obtain solution II; solution I is heated in an oil bath at 30-60°C and stirred continuously for 10-30 minutes, and then solution II is added, and the reaction is carried out for 12-24 hours to obtain a titanium source-coated Mo-based MOF compound composite material precursor.
[0020] Preferably, in step (5), the sintering temperature is 400-1000° C., the sintering time is 10-20 h, and the sintering atmosphere is nitrogen or argon or a mixed atmosphere of argon and hydrogen.
[0021] Compared with the prior art solutions, the present invention has the following advantages:
[0022] (1) The present invention uses a simple ion coordination method to firstly achieve in-situ growth and coating to achieve close combination of MoP and TiO2. Secondly, TiO2 can improve conductivity, facilitate the transmission of sodium ions, buffer volume expansion, and obtain a sodium ion battery MoP@TiO2 negative electrode material with excellent electrochemical performance by regulating the amount of titanium source. The material exhibits excellent electrochemical performance;
[0023] (2) In the present invention, low-toxic, green and environmentally friendly p-phenylene diphosphonic acid, phytic acid and phenylphosphonic acid are used as phosphorus sources, and tetraisopropyl titanate, tetrabutyl titanate and titanium tetrachloride are used as titanium sources to introduce titanium dioxide coating to maintain the morphology and structure, thereby improving the conductivity;
[0024] (3) The present invention does not use a traditional phosphorus source, but an organic phosphorus source, which supports the skeleton of the material during the synthesis of the precursor, can effectively inhibit the collapse of the material structure during the charge and discharge process, and maintain structural stability;
[0025] (4) The preparation method of the present invention is simple and easy to operate, the synthesis conditions are mild and easy to control, it is environmentally friendly, and the preparation cycle is short. It avoids the complex process of synthesizing Mo-based compounds first and then performing gas-solid reaction phosphating, and achieves fine control of the composite of MoP and materials such as titanium dioxide, which is easy to scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the XRD pattern of MoP@TiO2 prepared in Example 1 of the present invention;
[0027] Figure 2 This is a cycle performance diagram of a sodium ion battery assembled with the MoP@TiO2 composite material prepared in Example 1 of the present invention;
[0028] Figure 3This is a rate performance diagram of a sodium ion battery assembled with the MoP@TiO2 composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] Embodiment 1
[0031] A method for preparing a sodium ion negative electrode material MoP@TiO2 comprises the following steps:
[0032] (1) 0.24 g (0.001 mol) of sodium molybdate and 0.14 g (0.006 mol) of p-phenylene diphosphoric acid were dispersed in 20 ml of deionized water, and the mixture was rapidly stirred at room temperature for 10 min to form a uniform mixed solution; the concentrations of sodium molybdate and p-phenylene diphosphoric acid in the mixed solution were 0.05 mol / L and 0.3 mol / L, respectively; (2) the pH of the mixed solution was adjusted to 1.0 with concentrated hydrochloric acid, and then the mixed solution was placed in a pressure tube, the reaction temperature was set to 100° C., and the reaction time was set to 15 h, so that the mixed solution in the pressure tube underwent a coordination heat reaction;
[0033] (3) cooling the pressure tube in step (2) to room temperature, opening the pressure tube, filtering and washing with deionized water for 5 times and with anhydrous ethanol for 3 times, and then drying in a vacuum atmosphere at 60° C. for 6 h to obtain a precursor Mo-based MOF compound;
[0034] (4) The precursor Mo-based MOF compound was stirred and dispersed in 20 ml of anhydrous ethanol. In order to prevent the hydrolysis of the titanium source, 0.2 ml of concentrated ammonia water was added to obtain solution I; 0.13 ml of tetraisopropyl titanate (the mass of which was 20% of the mass of the precursor Mo-based MOF compound) was dispersed in 20 ml of anhydrous ethanol to obtain solution II; solution I was heated at 45°C in an oil bath and stirred continuously for 10 min, then solution II was added and reacted for 24 h to obtain a titanium source-coated Mo-based MOF compound composite material precursor;
[0035] (5) The precursor prepared in step (4) was sintered at 700° C. in an argon atmosphere for 10 h to obtain a MoP@TiO2 composite material.
[0036] The MoP@TiO2 composite material prepared in Example 1 was characterized and tested. Figure 1 The XRD results show that the composite material is pure phase MoP.
[0037] The electrochemical performance of the MoP@TiO2 composite material prepared in Example 1 was tested to determine its optimality as a negative electrode material for sodium ion batteries. The counter electrode tested was a metal sodium sheet, 1M sodium perchlorate (NaClO4) dissolved in a mixture of ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (1:1:1 vol / vol) containing 2wt% fluoroethylene carbonate additive (FEC). Figure 2 As can be seen from the figure, at a current density of 1C, the sodium battery has 943.5mAh g -1 After 100 cycles, the capacity remained at 290 mAh g -1 .from Figure 3 It can be seen that the MoP@TiO2 composite material prepared in this example still has a capacity of 100 mAh g at 5C rate. -1 The composite material exhibits the best cycle performance, rate performance and high-rate cycle performance.
[0038] Embodiment 2
[0039] A method for preparing a sodium ion negative electrode material MoP@TiO2 comprises the following steps:
[0040] (1) 1.24 g (0.001 mol) of ammonium molybdate and 1.33 g (0.002 mol) of phytic acid were dispersed in 20 ml of deionized water and rapidly stirred at room temperature for 10 min to form a uniform mixed solution; the concentrations of ammonium molybdate and phytic acid in the mixed solution were 0.05 mol / L and 0.3 mol / L, respectively;
[0041] (2) adjusting the pH of the mixed solution to 1.0 with concentrated hydrochloric acid and then placing it into a pressure tube, setting the reaction temperature to 120° C. and the reaction time to 20 h, so that the mixed solution in the pressure tube undergoes coordination heat reaction;
[0042] (3) cooling the pressure tube in step (2) to room temperature, opening the pressure tube, filtering and washing with deionized water for 5 times and with anhydrous ethanol for 1 time, and then drying in a vacuum atmosphere at 60° C. for 8 h to obtain a precursor Mo-based MOF compound;
[0043] (4) The precursor Mo-based MOF compound was stirred and dispersed in 20 ml of anhydrous ethanol. In order to prevent the hydrolysis of the titanium source, 0.2 ml of concentrated ammonia water was added to obtain solution I; 0.24 ml of titanium tetrachloride (the mass of which was 45% of the mass of the precursor Mo-based MOF compound) was dispersed in 20 ml of anhydrous ethanol to obtain solution II; solution I was heated at 30°C in an oil bath and stirred continuously for 30 min, then solution II was added and reacted for 12 h to obtain a titanium source-coated Mo-based MOF compound composite material precursor;
[0044] (5) Sintering the precursor prepared in step (4) at 400° C. in an argon atmosphere for 20 h to obtain a MoP@TiO2 composite material.
[0045] The electrochemical performance of the composite material prepared in this embodiment was tested in the same manner as in Example 1. The test results showed that at a current density of 1C, the sodium battery had a capacity of 869.5 mAh g -1 After 100 cycles, the capacity remained at 215 mAh g -1 In addition, the composite material still has 112 mAh g at 5C rate. -1 The composite material exhibits the best cycle performance, rate performance and high-rate cycle performance.
[0046] Embodiment 3
[0047] A method for preparing a sodium ion negative electrode material MoP@TiO2 comprises the following steps:
[0048] (1) 0.24 g (0.001 mol) of sodium molybdate and 0.158 g (0.001 mol) of phenylphosphonic acid were dispersed in 20 ml of deionized water, and the mixture was rapidly stirred for 10 min at room temperature to form a uniform mixed solution; the concentrations of sodium molybdate and phenylphosphonic acid in the mixed solution were 0.05 mol / L and 0.05 mol / L, respectively;
[0049] (2) adjusting the pH of the mixed solution to 3.0 with concentrated hydrochloric acid and then placing it into a pressure tube, setting the reaction temperature to 200° C. and the reaction time to 10 h, so that the mixed solution in the pressure tube undergoes coordination heat reaction;
[0050] (3) cooling the pressure tube in step (2) to room temperature, opening the pressure tube, filtering and washing with deionized water twice and anhydrous ethanol three times, and then drying in a vacuum atmosphere at 100° C. for 6 h to obtain a precursor Mo-based MOF compound;
[0051] (4) The precursor Mo-based MOF compound was stirred and dispersed in 20 ml of anhydrous ethanol. In order to prevent the hydrolysis of the titanium source, 0.2 ml of concentrated ammonia water was added to obtain solution I; 0.4 ml of tetrabutyl titanate (the mass of which was 60% of the mass of the precursor Mo-based MOF compound) was dispersed in 20 ml of anhydrous ethanol to obtain solution II; solution I was heated at 60° C. in an oil bath and stirred continuously for 10 min, then solution II was added and reacted for 24 h to obtain a titanium source-coated Mo-based MOF compound composite material precursor;
[0052] (5) Sintering the precursor prepared in step (4) at 1000° C. for 10 h in an argon atmosphere to obtain a MoP@TiO2 composite material.
[0053] The electrochemical performance of the composite material prepared in this example was tested in the same manner as in Example 1. The test results showed that at a current density of 1C, the sodium battery had a capacity of 821.5 mAh g -1 After 100 cycles, the capacity remained at 232 mAh g -1 In addition, the composite material still has 90 mAh g at 5C rate. -1 The composite material exhibits the best cycle performance, rate performance and high-rate cycle performance.
Claims
1. A method for preparing a sodium ion negative electrode material MoP@TiO2, characterized in that: The following steps are involved: (1) dispersing a molybdenum source and a phosphorus source into deionized water, and stirring at room temperature to form a uniform mixed solution; the molybdenum source is one of sodium molybdate, ammonium molybdate, and molybdenum chloride; the phosphorus source is one of p-phenylene diphosphonic acid, phytic acid, and phenylphosphonic acid; (2) adjusting the pH of the mixed solution to 1-3 and then loading it into a pressure tube, setting the reaction temperature and reaction time to carry out the coordination reaction; (3) washing and drying the mixed solution after the reaction in step (2) to obtain a Mo-based MOF compound; (4) adding a titanium source to the Mo-based MOF compound to obtain a titanium source-coated Mo-based MOF compound composite material precursor; (5) The precursor prepared in step (4) is subjected to high-temperature sintering heat treatment in a sintering atmosphere to obtain a MoP@TiO2 composite material.
2. The method for preparing a sodium ion negative electrode material MoP@TiO2 according to claim 1, characterized in that: In step (1), the concentrations of the molybdenum source and the phosphorus source in the mixed solution are 0.05-0.3 mol / L respectively.
3. The method for preparing a sodium ion negative electrode material MoP@TiO2 according to claim 1 or 2, characterized in that: In step (2), the reaction temperature is 100-200° C. and the reaction time is 10-20 h.
4. The method for preparing a sodium ion negative electrode material MoP@TiO2 according to claim 1 or 2, characterized in that: In step (2), the pH value of the mixed solution is adjusted by concentrated hydrochloric acid.
5. The method for preparing a sodium ion negative electrode material MoP@TiO2 according to claim 1 or 2, characterized in that: In step (3), the mixed solution after the reaction in step (2) is washed with deionized water for 2-5 times and with anhydrous ethanol for 1-3 times, and then dried in a vacuum atmosphere at 60-100° C. for 6-8 hours.
6. The method for preparing a sodium ion negative electrode material MoP@TiO2 according to claim 1 or 2, characterized in that: In step (4), the titanium source is 20-60% of the mass of the Mo-based MOF compound.
7. The method for preparing a sodium ion negative electrode material MoP@TiO2 according to claim 1 or 2, characterized in that: In step (4), the titanium source is one of tetraisopropyl titanate, tetrabutyl titanate, and titanium tetrachloride.
8. The method for preparing a sodium ion negative electrode material MoP@TiO2 according to claim 1 or 2, characterized in that: In step (4), the Mo-based MOF compound is dispersed in anhydrous ethanol with stirring, and concentrated ammonia water is added to obtain solution I; the titanium source is dispersed in anhydrous ethanol to obtain solution II; solution I is heated in an oil bath at 30-60° C. and stirred continuously for 10-30 min, and then solution II is added, and the reaction is carried out for 12-24 h to obtain a titanium source-coated Mo-based MOF compound composite material precursor.
9. The method for preparing a sodium ion negative electrode material MoP@TiO2 according to claim 1 or 2, characterized in that: In step (5), the sintering temperature is 400-1000° C., the sintering time is 10-20 hours, and the sintering atmosphere is nitrogen or argon or a mixed atmosphere of argon and hydrogen.
Citation Information
Patent Citations
Molybdenum phosphide catalyst and preparation method thereof
CN111672527A
Metal phosphide as well as preparation method and application thereof
CN112125289A